2004
DOI: 10.4141/a03-070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pilgrim, Hungarian, Chinese, Synthetic and Embden strains of geese and their crosses for body weight

Abstract: The Pilgrim, Hungarian, Chinese, Selected C hinese, Synthetic (developed from Pilgrim, Chinese and Hungarian), Selected Synthetic, Large Embden and Small Embden strains of geese raised from 1980 to 1988 at the Greenbelt farm of the Centre for Food and Animal Research (formerly Animal Research Centre, and Animal Research Institute) in Ottawa, Canada varied significantly in body weight at 9 and 16 wk of age. The Large Embden strain weighed more than the Small Embden strain in 1986, and both were heavier than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
1
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
3
1
0
Order By: Relevance
“…In the present study, the Small Embden-sired selected strain crosses weighed more at 9 and 16 wk of age than the Selected Chinese and Synthetic strains, in agreement with observations of Shrestha et al (2004a). The authors also reported that the heterosis estimate was negligible for Small Embden × Selected Chinese strain cross, and 4-8% for the Small Embden × Selected Synthetic strain cross.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the present study, the Small Embden-sired selected strain crosses weighed more at 9 and 16 wk of age than the Selected Chinese and Synthetic strains, in agreement with observations of Shrestha et al (2004a). The authors also reported that the heterosis estimate was negligible for Small Embden × Selected Chinese strain cross, and 4-8% for the Small Embden × Selected Synthetic strain cross.…”
Section: Discussionsupporting
confidence: 79%
“…The Large Embden × Selected Chinese strain cross was not only heavier than the Selected Chinese strain, but also weighed more than the Small Embden-sired Selected Chinese and Synthetic strain crosses that were similar, and these strain crosses were heavier in body weights at 9 and 16 wk of age than their respective female parent strains, in agreement with Shrestha et al (2004a). The Large Embden strain compared with the Small Embden strain when mated to Selected Chinese strain was 0.9 kg heavier in body weight at 16 wk of age along with 2% more total fat.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations